PENERAPAN TEKNOLOGI MOBILE LEARNING ( POWTOON ) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MI MUHAMMADIYAH BUNTU BARANA - Rizlahani; Imam Akbar; Fuad Danindra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
RIZLAHANI, 2026. The Implementation of Mobile Learning Technology (Powtoon) to Improve the Learning Outcomes of Fourth Grade Students at MI Muhammadiyah Buntu Barana. Thesis. Supervisor I: Imam Akbar, S.Kom., M.Kom., and Supervisor II: Fuad Danindra, S.Kom., M.I.Kom. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Enrekang. This study aimed to determine the process of implementing mobile learning technology (Powtoon) to improve the learning outcomes of fourth grade students at MI Muhammadiyah Buntu Barana. This research employed Classroom Action Research (CAR) conducted through the stages of planning, action implementation, observation, and reflection. The subjects of this study were all fourth grade students. The data collection technique was carried out through tests to measure students’ learning outcomes during the learning process. The results of the study showed that the implementation of mobile learning technology (Powtoon) was able to improve students’ learning outcomes. This can be seen from the increase in students’ learning mastery in each learning cycle. The conclusion of this study is that the implementation of mobile learning technology (Powtoon) is effective in improving students’ learning outcomes in the Indonesian language subject, particularly on conjunction material, at the elementary school level.